2019
DOI: 10.1089/met.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and Its Associations with Metabolism and Physical Activity in a Latino Sample

Abstract: Background: Brain-derived neurotrophic factor (BDNF) is associated with body weight and other health conditions but remains understudied in the Latino population. The aim of this study was to examine the associations of BDNF serum levels with body mass index (BMI), physical activity, and the rs6265 nonconservative polymorphism among 349 Latinos aged ≥18 years enrolled in the Arizona Insulin Resistance Registry. Materials and Methods: Data on physical activity were acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Combining 12 effect sizes from 8 studies 7 , 20 , 23 25 , 29 , 31 , 35 included 1400 participants showed that the overall correlation between BDNF levels and FBG was not statistically significant (overall Fisher’s Z = 0.05; 95%CI − 0.21, 0.11), as shown in Fig. 3 .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Combining 12 effect sizes from 8 studies 7 , 20 , 23 25 , 29 , 31 , 35 included 1400 participants showed that the overall correlation between BDNF levels and FBG was not statistically significant (overall Fisher’s Z = 0.05; 95%CI − 0.21, 0.11), as shown in Fig. 3 .…”
Section: Resultsmentioning
confidence: 94%
“…Fourteen studies have reported the average serum/plasma BDNF values patients with glycemic disorders vs. healthy controls 7 , 20 25 , 27 30 , 32 , 33 , 35 . Eight articles have depicted the correlation between FBG and serum/plasma BDNF levels 7 , 20 , 23 25 , 29 , 31 , 35 ; 6 investigations have explored the correlation between HOMA-IR and BDNF concentrations 7 , 20 , 22 25 . Also, 4 and 2 studies have respectively reported the correlation between serum/plasma BDNF levels with HbA1c and immunoreactive insulin (IRI) 7 , 23 , 25 , 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Нейротрофическая активность BDNF и его роль в воспалении, метаболизме и патогенезе сердечно-сосудистых заболеваний объединены термином «триакт», который объясняет взаимодействия между мозгом, иммунной системой и жировой тканью и их роль в развитии кардиометаболических заболеваний [46]. Имеются данные о том, что уровень данного фактора тесно взаимосвязан с повышенной массой тела, ожирением, сахарным диабетом 2-го типа и развитием метаболического синдрома [47]. В экспериментальных условиях продемонстрировано, что повышение уровня BDNF улучшает метаболическую регуляцию посредством влияния на чувствительность гепатоцитов к инсулину и функцию β-клеток поджелудочной железы [48].…”
Section: семейство нейротрофинов и их роль в патофизиологии бронхиальной астмы сочетанной с ожирениемunclassified
“…Decreased activity-dependent secretion from the neurons of BDNF Met carriers is functionally significant because most BDNF protein is released from the CASPS2 activity-dependent pathway [ 77 ]. This polymorphism is the most studied and has been associated with various age-related diseases, such as PD, AD, T2D and also depression [ 33 , 34 , 58 , 60 , 98 ].…”
Section: Bdnf Genetic Polymorphismsmentioning
confidence: 99%